Relationship Between Erythrocyte Index Values And Serum Ferritin Levels In Anemia At The Pathological Laboratory - Listina, Osie (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Anemia is a medical condition characterized by low levels of hemoglobin in the blood, which can lead to symptoms such as fatigue, dizziness, pale skin, and the body's inability to transport oxygen efficiently enough. Anemia can be caused by various factors, including iron deficiency, vitamin B12 deficiency, genetic disorders, and chronic diseases. Recent research and data are also presented to provide a better understanding of the prevalence and impact of anemia in the global population. This study was conducted on 94 people suffering from anemia who were treated at Dr. Tadjuddin Chalid Hospital based on patient medical records for the period January 2022 - June 2023. This study is a retrospective observational descriptive study on anemia patients from medical records treated at Dr. Tadjuddin Chalid Hospital. Data analysis was processed using SPSS software. The results of this study indicate the distribution of anemia patients treated at Dr. Tadjuddin Chalid Hospital Makassar for the period January 2022 - June 2023, namely. Of the total sample of 94 people who suffered from anemia, there were 47 male patients (50%) and 47 female patients (50%). The results and conclusions that were obtained in patients with iron deficiency anemia with low MCV and MCH erythrocyte levels, while the MCHC erythrocyte levels cannot be used as a measure of someone affected by iron deficiency anemia and low serum ferritin levels are a strong sign of iron deficiency anemia.